2007
DOI: 10.1007/s10397-006-0262-5
|View full text |Cite
|
Sign up to set email alerts
|

Use of the BiClamp (a bipolar coagulation forceps) in gynecological surgery

Abstract: The integration of new technical possibilities into the overall concept is the determining factor in progress in surgery. The availability of the BiClamp and its specially designed electrical concept mean that we now have a new bipolar coagulation forceps at our disposal. Based on the principles of electrosurgery, we developed a new current modulation that has improved hemostatic properties. The new current modulation can be used for bipolar laparoscopic coagulation forceps, and also for new types of forceps f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
1
3
0
1
Order By: Relevance
“…6 Zubke et al evaluated the BiClamp Device and showed a 21% decrease in OR time and decreased blood loss. 9 Hefni et al 4 and Cronze and Coning 1 showed similar results. A labial burn was the only complication noted in two studies.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…6 Zubke et al evaluated the BiClamp Device and showed a 21% decrease in OR time and decreased blood loss. 9 Hefni et al 4 and Cronze and Coning 1 showed similar results. A labial burn was the only complication noted in two studies.…”
Section: Discussionsupporting
confidence: 75%
“…9 Surgeons are always seeking improvements in techniques that improve the patient's surgical experience.…”
Section: Discussionmentioning
confidence: 99%
“…Without the BiClamp device, several patients in the present study would have required abdominal surgery because of the size of their uterus or the lack of access/descent. Zubke et al . describe the BiClamp device as being particularly good in technically challenging cases where access is limited.…”
Section: Discussionmentioning
confidence: 99%
“…Various types of VSDs are described in the literature, including the LigaSure™ (5,20), Enseal® (15,17) marSeal (13,14), BiClamp® (31), and Sonicision™ cordless ultra-sonic dissector (24). In 2012 a new VSD called Caiman® (Aesculap® -a B. Braun company, Aesculap AG, Tuttlingen, Germany) was introduced into the market and approved by the Food and Drug Administration for vessels up to 7 mm in diameter (7).…”
Section: Introductionmentioning
confidence: 99%